2019
DOI: 10.3390/ani9110937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Apple Polyphenols Supplementation on Hepatic Fat Deposition and Antioxidant Capacity in Finishing Pigs

Abstract: Simple SummaryExcessive fat deposition (5–10%) in the liver could lead to liver damage and nonalcohol fatty liver disease (NAFLD). However, there is no satisfactory safe and effective measure of preventive and therapeutic treatments so far. Thus, the prevention of excessive fat deposition through diet modification might be a better strategy to protect humans from metabolic diseases. Due to the anatomical and physiological similarities between humans and pigs, the present study took the finishing pig as an anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…Hepatocellular steatosis is a characteristic of NAFLD. More than 5% of hepatocyte steatosis is necessary for the diagnosis of NAFLD [25,26]. In addition, it has been reported that exacerbations of steatosis are positively correlated with lobular inflammation, zone-3 fibrosis, and definite steatohepatitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular steatosis is a characteristic of NAFLD. More than 5% of hepatocyte steatosis is necessary for the diagnosis of NAFLD [25,26]. In addition, it has been reported that exacerbations of steatosis are positively correlated with lobular inflammation, zone-3 fibrosis, and definite steatohepatitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical observation that increased intake of apples (rich in quercetin) protects against abdominal aortic calcification in older women 160 aligns with experimental data. Indeed, apple polyphenols, the major antioxidants in apples, have been shown to possess wide-ranging beneficial biological functions that could benefit patients with CKD 161 . In dipterans, acute treatment with quercetin has already been demonstrated to be geroprotective 162 and in a rat model of CKD quercetin protects kidney function 163 .…”
Section: Nutrients That Target Senescencementioning
confidence: 99%
“…For instance, apple polyphenols have the potential to be hepatoprotective and inhibit hepatic steatosis [ 25 ]. As a feed additive for pigs, apple polyphenols can reduce fat deposits in the liver of finishing pigs, improve lipid distribution, and strengthen the distribution of antioxidant enzymes [ 26 ]. Moreover, apple polyphenols are potentially effective dietary supplements and protect the stomach lining from damage by aspirin [ 27 ], protect colonic mucosa in ulcerative colitis [ 28 ], and reduce inflammatory processes, which lead to bowel disease [ 29 ].…”
Section: Polyphenolsmentioning
confidence: 99%